OBSERVATION ON THE FOOD AND FEEDING HABITS OF SOME FLATFISHES OF ORISSA COAST - Datta, N C; Das, M (Indian Journal of Fisheries, 2011)
The Cynogiossids, Cynoglossus arel, C. lingua, C. biljneatus and Paraplaguisablochii, are purely carnivorous iii nature, their food comprising mainly polychaetes,crustaceans and molluscs. A remarkable shift in their feeding habit with theincrease of body length is observed from the index of preponderance of differentfood items. While fishes of smaller body length prey mainly upon the amphipods,the larger ones mainly feed upon other crustaceans. Seasonal variation of differentfood items has also been observed.